Tenancy Rent Control and Credible Commitment in Maintenance - Richard J. Arnott; Elizaveta Shevyakhova (Center for Economic Studies and ifo Institute (CESifo), 2014)
Under tenancy rent control, rents are regulated within a tenancy but not between tenancies. This paper investigates the effects of tenancy rent control on housing quality and maintenance. Since the discounted revenue received over a fixed-duration tenancy depends only on the starting rent, intuitively the landlord has an incentive to spruce up the unit between tenancies in order to show it well, but little incentive to maintain the unit well during the tenancy. The paper formalizes this intuition and presents numerical examples illustrating the efficiency loss from this effect.
Keywords: R21; R31; R38; 330; tenancy rent control; rent control; maintenance; housing quality; credible commitment